Wildfire and forest treatments mitigate—but cannot forestall—climate-driven changes in streamflow regimes in a western US mountain landscape - Furniss, Tucker J; Hessburg, Paul F; Churchill, Derek; Wigmosta, Mark; Povak, Nicholas; Duan, Zhuoran; Brion Salter, R (Environmental research letters, 2025)
Warming temperatures and increasingly variable precipitation patterns are reducing winter snowpack and critical late-season streamflows. Here, we used two models (LANDIS-II and DHSVM) in linked simulations to evaluate the effects of wildfire and forest management scenarios on future snowpack and streamflow dynamics. We characterized the biophysical attributes of the areas with the greatest potential for treatments to improve hydrologic functioning and we examined projected trends in flow regimes over the 21st century. We found that, despite a projected increase in total annual flows, there was a steep decline in snowpack and late-season flows. Wildfire was an important factor influencing streamflow and snowpack dynamics, with increasing burned area partially offsetting climate-driven declines in snowpack and spring flows. Forest thinning treatments contributed modest increases to annual flows, although effects were overshadowed by the influences of climate and wildfire. Warming winter temperatures extinguished snowmelt-driven flows in low- and mid-elevation watersheds, causing a transition from spring snowmelt- to autumn rain-dominated streamflow regimes. Our results complement prior empirical studies showing that forest treatments can improve snowpack retention and annual streamflow, and they emphasize the importance of wildfire as a primary factor governing landscape hydrology. We found that neither land management practices nor wildfire could completely compensate for the top–down controls of future climate on landscape hydrology. Declines in snowpack retention and a regime shift in the timing of peak flows will have dramatic consequences for forest health, human water resources, and Pacific salmon populations.